2008
DOI: 10.1021/la800591n
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Vapor-Deposited Thin Silica Film: Morphological and Spectral Characterization

Abstract: Surface modification reactions by organosilicon compounds have demonstrated great success in a wide variety of applications. However, they are of limited usefulness in that they only proceed appreciably on surfaces that have an abundance of reactive hydroxyl groups, thus preventing their application to some materials of technological relevance, such as plastics and polymers. A process capable of depositing a surface rich in reactive hydroxyl groups onto a wide variety of substrates could potentially enable the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
6
9
0
Order By: Relevance
“…When the silica surface was treated with poly(ethylene oxide), the isotherm thickness and the structure of the adsorbed water layers was altered significantly. 33 Similar deviations were observed for water adsorption in porous silica films. 33 Octadecylsilane SAMs are often produced on silica surfaces to obtain water repellency because this SAM gives a water contact angle higher than 90°.…”
Section: Adsorption Isothermssupporting
confidence: 70%
See 2 more Smart Citations
“…When the silica surface was treated with poly(ethylene oxide), the isotherm thickness and the structure of the adsorbed water layers was altered significantly. 33 Similar deviations were observed for water adsorption in porous silica films. 33 Octadecylsilane SAMs are often produced on silica surfaces to obtain water repellency because this SAM gives a water contact angle higher than 90°.…”
Section: Adsorption Isothermssupporting
confidence: 70%
“…33 Similar deviations were observed for water adsorption in porous silica films. 33 Octadecylsilane SAMs are often produced on silica surfaces to obtain water repellency because this SAM gives a water contact angle higher than 90°. Although well-defined covalently attached silane SAMs can be reproducibly prepared, there is always disorder in the alkyl chain packing.…”
Section: Adsorption Isothermssupporting
confidence: 70%
See 1 more Smart Citation
“…[17][18][19][20] However, most published investigations have concerned the simple vapourphase reaction of aminosilanes with a hydroxylated surface, usually glass or silicon at high temperatures that are not suitable for COP chips. 21,22 In contrast to the multi-step complexity of the methods described above, we have found that a fast and simple route to versatile amine-functionalized surfaces on COP plastics is to combine the oxygen plasma activation method with plasma enhanced chemical vapour deposition (PECVD) from an aminated precursor. PECVD, a single step high throughput process, is a versatile surface engineering technique which has proven to be an excellent tool for surface modification and large scale production that does not leave behind liquid waste.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously investigated the deposition process and characterized the surface chemistry of thin silica films formed by the room-temperature, vapor-phase hydrolysis of tetrachlorosilane . We have also demonstrated that these films support organosilane surface modification chemistries using conventional solvent techniques, resulting in monolayers with thermal and aqueous immersion stability properties indistinguishable from those deposited on native silicon oxide surfaces .…”
Section: Background and Introductionmentioning
confidence: 99%